Grisel`s syndrome presenting with neck pain: an atypical case - Bilgin, Emre; Çavuş, Gökhan; Açık, Vedat; Gezercan, Yurdal; Ökten, Ali İhsan (The Turkish Journal of Pediatrics, 2020)
Grisel`s syndrome is non-traumatic inflammatory subluxation of the atlantoaxial joints presenting clinically as torticollis, neck pain, and reduced neck mobility. Several pathogens have been implicated in its etiology. Early diagnosis and treatment are vital for Grisel`s syndrome to avoid serious neurological complications. This study reports the case of a 6-year-old girl who complained of pain and curvature of the neck following an upper respiratory tract influenza infection. Notably, the patient`s neck pain and curvature worsened toward the end of her normal day for a week. This pattern is rare, but it represents an important example of Grisel`s syndrome as a condition that varies through the day.